Study of Spatiotemporal Development of Global Distribution of Magnetospheric ELF/VLF Waves Using Ground‐Based and Satellite Observations, and RAM‐SCB Simulations, for the March and November 2017 Storms. Issue 2 (21st February 2021) - Takeshita, Yuhei; Shiokawa, Kazuo; Miyoshi, Yoshizumi; Ozaki, Mitsunori; Kasahara, Yoshiya; Oyama, Shin‐ichiro; Connors, Martin; Manninen, Jyrki; Jordanova, Vania K.; Baishev, Dmitry; Oinats, Alexey; Kurkin, Vladimir
Abstract: Magnetospheric Extremely Low‐Frequency/Very Low‐Frequency (ELF/VLF) waves have an important role in the acceleration and loss of energetic electrons in the magnetosphere through wave‐particle interaction. It is necessary to understand the spatiotemporal development of magnetospheric ELF/VLF waves to quantitatively estimate this effect of wave‐particle interaction, a global process not yet well understood. We investigated spatiotemporal development of magnetospheric ELF/VLF waves using 6 PWING ground‐based stations at subauroral latitudes, Exploration of energization and Radiation in Geospace and RBSP satellites, POES/MetOp satellites, and the RAM‐SCB model, focusing on the March and November 2017 storms driven by corotating interaction regions in the solar wind. Our results show that the ELF/VLF waves are enhanced over a longitudinal extent from midnight to morning and dayside associated with substorm electron injections. In the main to early storm recovery phase, we observe continuous ELF/VLF waves from ∼0 to ∼12 MLT in the dawn sector. This wide extent seems to be caused by frequent occurrence of substorms. The wave region expands eastward in association with the drift of source electrons injected by substorms from the nightside. We also observed dayside ELF/VLF wave enhancement, possibly driven by magnetospheric compression by solar wind, over an MLT extent of at least 5 h. Ground observations tend not to observe ELF/VLF waves in the post‐midnight sector, although other methods clearly show the existence of waves. This is possibly due to Landau damping of the waves, the absence of the plasma density duct structure, and/or enhanced auroral ionization of the ionosphere in the post‐midnight sector. Plain Language Summary: Extremely Low‐Frequency/Very Low‐Frequency (ELF/VLF) waves from the Earth's magnetosphere play an important role in the acceleration and loss of energetic electrons in the radiation belts through wave‐particle interactions. In order to understand, and possibly to predict, the development and decay of hazardous radiation belt particles, it is necessary to understand spatiotemporal development of magnetospheric ELF/VLF waves. In this paper, we investigated spatiotemporal development of magnetospheric ELF/VLF waves using six ground‐based stations, which are longitudinally distributed at subauroral latitudes, three satellites in the inner magnetosphere, several satellites in the ionosphere, and global simulation modeling, focusing on the March and November 2017 geomagnetic storms. Our results show that the ELF/VLF waves are enhanced over a longitudinal extent from midnight to morning and dayside associated with substorm electron injections. In the main to early storm recovery phase, we observe continuous ELF/VLF waves from ∼0 to ∼12 magnetic local time in the dawn sector. The wave region expands eastward in association with eastward drift of source electrons injected by substorms from the nightside. We also observed dayside wave enhancement, possibly driven by magnetospheric compression by solar wind, over a local time extent of at least 5 h. Key Points: The global distribution of magnetospheric Extremely Low‐Frequency/Very Low‐Frequency (ELF/VLF) waves was obtained from ground‐based and satellite observations, and RAM‐SCB simulation The source region of magnetospheric ELF/VLF wave longitudinally expands in association with substorm injections and eastward electron drift ELF/VLF waves driven by magnetospheric compression were observed with a longitudinal extent of at least 5 MLT